2018
DOI: 10.1093/rpd/ncy212
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Abdominal Ct Radiation Dose and Image Quality

Abstract: The aim of this study was to evaluate how iterative reconstruction can compensate for the noise increase in low radiation dose abdominal computed tomography (CT) technique for large size patients and the general impact of obesity on abdominal organ doses and image quality in CT. An anthropomorphic phantom layered with either none or a single layer of 3-cm- thick circumferential animal fat packs to simulate obese patients was imaged using a 128MDCT scanner. Abdominal protocols (n = 12) were applied using automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Despite active dose-modulation, higher BMI is usually associated with lower EID-CT image quality due to higher image noise [25]. Our study reports similar findings for PCD-CT datasets: patients with higher BMI-values exhibited significantly higher image noise on both CT systems and at all analyzed PCD-VMI keV levels.…”
Section: Discussionsupporting
confidence: 85%
“…Despite active dose-modulation, higher BMI is usually associated with lower EID-CT image quality due to higher image noise [25]. Our study reports similar findings for PCD-CT datasets: patients with higher BMI-values exhibited significantly higher image noise on both CT systems and at all analyzed PCD-VMI keV levels.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, DLR may be useful, especially for ultra-highresolution CT that requires higher computation power (38). In addition, the image noise is substantially increased at low radiation doses, especially when large objects are scanned (39). We found no significant correlation between the CTDI vol /BMI value and the difference in the noise, indicating that DLR yielded similar noise reduction effects irrespective of the radiation dose and the patient habitus.…”
Section: Calculation Timesmentioning
confidence: 76%
“…27 It has been reported that with the increase of cross-sectional dimensions of patients, the tube current in ATCM will increase accordingly to ensure the quality of CT images and may result in the increase of absorbed dose. 28 Hence, we compared the abdominal size of these patients by measuring the abdominal fat ratio (AFS) values, 29 which refers to the distance from the anterior spine to the anterior abdominal wall divided by the maximum distance from the outer edge of the rectus sheath to the dermis in the same CT image. To some extent, AFS also indicates the fat layer thickness/body circumference of a pregnant woman during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…ATCM is aimed to adjust the tube current according to the attenuation characteristics of the patient on the premise of ensuring good image quality as well as reducing the radiation exposure 27 . It has been reported that with the increase of cross‐sectional dimensions of patients, the tube current in ATCM will increase accordingly to ensure the quality of CT images and may result in the increase of absorbed dose 28 . Hence, we compared the abdominal size of these patients by measuring the abdominal fat ratio (AFS) values, 29 which refers to the distance from the anterior spine to the anterior abdominal wall divided by the maximum distance from the outer edge of the rectus sheath to the dermis in the same CT image.…”
Section: Discussionmentioning
confidence: 99%